Sweetpotato support platforms to build a community of practice - International Potato Center (2012)
Three Sweetpotato Support Platforms (SSPs), located in Eastern, Southern, and West Africa are developing tools and strategies for sharing information and efficiencies to create a dynamic and cost-effective community of practice among researchers and development agents across multiple disciplines and countries. Through the Reaching Agents of Change (RAC) project, launched in June 2011, they also aim to raise the profile of vitamin A-rich sweetpotato through advocacy and build capacity among partners to effectively implement Sweetpotato-based development efforts.